Implications of EU enlargement on the EU greenhouse gas "bubble" and internal burden sharing - Axel Michaelowa; Regina Betz (Hamburg Institute of International Economics (HWWA), 2000)
Currently, the EU-15 forms the only bubble under the Kyoto Protocol and has negotiated an internal burden sharing. A strategic EU climate policy should include accession countries. Thus, even in the case of early ratification of the Kyoto Protocol by 2002, it would be sensible to form a bubble with all countries that are certain to be EU members during the commitment period 2008-2012. Of course due to Art. 4,4 of the Protocol the EU-15 has to stick to its own bubble. However, nothing prevents it from forming an implicit bubble including all first wave countries by inducing them to form a bubble on their own and transfer the surplus to the EU-15. Similarly, second wave countries should form a bubble of their own to co-ordinate JI and permit transfers to the EU. This would reduce the gap between business-as-usual and the target by about 50%. If ratification is delayed to a point where it is clear which second wave countries will be members by 2008, the bubble should be extended by those countries. When in 2005 target negotiations start for the second commitment period, the EU should negotiate a bubble consisting of all states being certain to be members by 2013. – – Derzeit ist die EU der 15 die einzige Emissionsgemeinschaft nach den Regeln des Kyoto-Protokolls und hat eine interne Lastenteilung vereinbart. Eine strategische EUKlimapolitik sollte die Beitrittsländer einschließen. Selbst im Fall einer frühzeitigen Ratifizierung des Kyoto-Protokolls wäre es sinnvoll, eine Emissionsgemeinschaft mit allen Ländern abzuschließen, die in der Zielperiode 2008-2012 EU-Mitgliedsländer sein werden. Aufgrund Art. 4,4 des Protokolls muss die EU der 15 ihre Emissionsgemeinschaft aufrechterhalten. Jedoch hindert sie nichts daran, eine implizite Emissionsgemeinschaft mit den Ländern der ersten Beitrittswelle zu bilden, indem diese eine eigene Gemeinschaft bilden und den Überschuß an die EU der 15 weitergeben. Gleichermaßen sollten auch die Länder der zweiten Beitrittswelle eine Gemeinschaft bilden, um ihre Transfers an die EU abzustimmen. Dies würde den Abstand zwischen "weiter so" und dem Kyoto-Ziel um ca. die Hälfte verringern. Wenn die Ratifizierung so lange verzögert wird, daß klar ist, welche Länder der zweiten Welle 2008 EUMitglied sein werden, sollte die Gemeinschaft entsprechend erweitert werden. Bei den 2005 beginnenden Verhandlungen über Ziele für die zweite Budgetperiode sollte die EU eine Zielgemeinschaft für alle Länder anstreben, die 2013 sicher EU-Mitglied sein werden.
Keywords: 330; Klimaschutz; Luftverunreinigung; Kohlendioxid; EU-Erweiterung; Internationaler Transfer; EU-Staaten; Osteuropa